2006
DOI: 10.1124/jpet.106.111468
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effects of a Novel Iron Chelator, Pyridoxal 2-Chlorobenzoyl Hydrazone, in the Rabbit Model of Daunorubicin-Induced Cardiotoxicity

Abstract: Iron chelation is the only pharmacological intervention against anthracycline cardiotoxicity whose effectiveness has been well documented both experimentally and clinically. In this study, we aimed to assess whether pyridoxal 2-chlorobenzoyl hydrazone (o-108, a strong iron chelator) can provide effective protection against daunorubicin (DAU)-induced chronic cardiotoxicity in rabbits. First, using the HL-60 leukemic cell line, it was shown that o-108 has no potential to blunt the antiproliferative efficacy of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 46 publications
(46 reference statements)
1
13
0
Order By: Relevance
“…Nevertheless, this was well attributable to the hydrophilic nature of this drug, which hinders its penetration into the cardiomyocytes. On the other hand, using our in vivo rabbit model, we have recently shown that lipophilic aryolhydrazone iron chelators are able to protect against anthracycline cardiotoxicity in terms of overall mortality, functional parameters, and histopathology (Simunek et al, 2005a;Sterba et al, 2006Sterba et al, , 2007a. However, at the same time, it was revealed that dexrazoxane is superior to aroylhydrazones, as the cardioprotection of the latter compounds-albeit significant-was always only partial.…”
Section: Discussionmentioning
confidence: 84%
“…Nevertheless, this was well attributable to the hydrophilic nature of this drug, which hinders its penetration into the cardiomyocytes. On the other hand, using our in vivo rabbit model, we have recently shown that lipophilic aryolhydrazone iron chelators are able to protect against anthracycline cardiotoxicity in terms of overall mortality, functional parameters, and histopathology (Simunek et al, 2005a;Sterba et al, 2006Sterba et al, , 2007a. However, at the same time, it was revealed that dexrazoxane is superior to aroylhydrazones, as the cardioprotection of the latter compounds-albeit significant-was always only partial.…”
Section: Discussionmentioning
confidence: 84%
“…We used a lipophilic iron chelator salicylaldehyde isonicotinoyl hydrazone (SIH), an analog of pyridoxal isonicotinoyl hydrazone that shows high affinity and selectivity for iron (Richardson and Ponka, 1998b). These chelators have been used in a number of in vivo and in vitro models, and the dosage we used was based on previous in vivo work (Richardson and Ponka, 1998a;Klimtova et al, 2003;Simunek et al, 2005Simunek et al, , 2008aSterba et al, 2005Sterba et al, , 2006Sterba et al, , 2007. An SIH solution was prepared as reported previously (Klimtova et al, 2003).…”
Section: Animals Cpmentioning
confidence: 99%
“…SIH and o-108 prevented both premature deaths of animals as well as significantly improved the DAU-induced impairment of cardiac function (LV EF, dP/dt max ), biomarkers of cardiac injury (cTnT), as well as histopathological parameters (255,256). However, dose escalation of all the aroylhydrazone chelators did not provide additional protection, but on the contrary, it hampered virtually all the beneficial effects of the chelators regarding both overall mortality rate and cardioprotection (244,255,256). Importantly, these higher chelators' doses were nontoxic and well tolerated when administered to animals alone.…”
mentioning
confidence: 99%
“…as protectors against ANT-induced cardiotoxicity in vitro and/or in vivo (see below), have been also shown not to blunt the antiproliferative effects of ANTs in various cancer cell lines (209,243,256). It should be noted that-with the exception of few DEX analogs (108)-no chelator has been specifically designed for use in prevention of ANT cardiotoxicity.…”
mentioning
confidence: 99%
See 1 more Smart Citation